Intervensi Psikologi Untuk Meningkatkan Ekspresi Diri Anak Pendiam Pada Siswa Kelas III Sekolah Dasar Al-Munawaroh - Lutfiah, Nayla; Abidin, Yunus; Undayasari, Dwi (CV. SINAR HOWUHOWU, 2025)
This study airms to improve the self expresions of quite students through structured psychological interventions tailored to the needs of third grade students at SD AL-Munawarah. The intervention included play therapy, group guidance, and role playing activities designed to be supportive and engaging. The research used a Classrom Action Research (CAR) design conducted in one cycle over ten days. Threequite students ewre identified based on teacher observations and interviews. Data were collected using observations, interviws, and self expresions questionnaires administered before and after the the intervention. Result showed a 35% increase in self expression scores. student became more confident in speaking, participating in group work, and engagging with peers. Teachers reported improve emosional expression and clasroom interaction. The study concludes that psychological interventions can help quiet student express themselves better and contribute to a more inclusive, make student feels more comfortable, so that student get equal potential opportunities with other friend, and suppoortive classroom environment